Study of Corrosion Inhibitory Effects of Alcoholic Extracts of Tinospora Cordifolia on Metal Tin in Acidic Media HCl with and without Additive (KCl) - Mandawara, V.; Chaturvedi , A. (Journal of Scientific Research, 2023)
The corrosion inhibitory efficiency of Tinospora Cordifolia stem and leaf extract in different concentrations of HCl acid (0.5, 1, 2, and 3N) was examined using weight loss and thermometric methods in the absence and presence of an additive (KCl). According to the findings of this investigation, inhibition efficiency (ɳ%) rises with increasing inhibitor concentration as well as acid strength, and additional improvement in inhibition efficiency was found with the addition of additives (KCl) owing to a synergistic effect. According to the findings, stem extract is a better corrosion inhibitor than leaf extract. The maximum inhibition efficiency was observed for stem and leaf extracts (95.76 and 92.47 %) at their maximum concentrations (0.8 %) in the absence of an additive in the maximum strength of HCl acid (3N), while it was observed at 98.58 and 95.29 % in the presence of additive (3N KCl) of maximum strength.